Teaching Writing Using Electronic Portfolio in the Multimedia Lab at Widya Mandala Surabaya Catholic University - Wuri Soedjatmiko; Johanes Leonardi Taloko (TEFLIN, 2003)
This paper attempts to share the teaching of descriptive writing using electronic portfolio (e-portfolio) in the multimedia lab where students can write according to their own pace. Given indivi-dual electronic folders, they can continue writing whenever they want. The students can revise their first draft following comments given by the tutor or peers, or continue to the next assignment put in the tutors folder. Microsoft Word also provides tools,